1
$\begingroup$

Given the following:

$$\begin{pmatrix} 1 & 1 & 1 & ... & 1 \\ a_1 & a_2 & a_3 & ... & a_n \\ a_1^2 & a_2^2 & a_3^2 & ... & a_n^2 \\ \vdots & \vdots & \vdots & \vdots & \vdots \\ a_1^{n-1} & a_2^{n-1} & a_3^{n-1} & ... & a_n^{n-1}\end{pmatrix} \begin{pmatrix} x_1 \\ x_2 \\ x_3 \\ \vdots \\ x_n\end{pmatrix} = \begin{pmatrix} 0 \\ 0 \\ 0 \\ \vdots \\ 1 \end{pmatrix} $$

How can this be solved to give $x_k$? By Cramer's rule, this should be $x_k=\frac{\det(A_i)}{\det(A)}$

How can this result be simplified? Since this is a Vandermonde matrix, $\det(A)=\prod_{1\leq i<j\leq n}(a_j-a_i)$. However, can the numerator be written any simpler? In a paper where I have seen this equation system used, the result is given as: $x_k=\prod_{1\leq j \leq n,\;j \neq i} (a_i - a_j)^{-1}$ but it's not clear how the simplification has been achieved?

$\endgroup$
0
$\begingroup$

Using Cramer's rule, we know

$$x_k = \frac{\det(A_k)}{\det(A)}$$

Now, as we know the Vandermonde determinant is equal to

$$\det(A)=\prod_{1\leq i<j\leq n}(a_j-a_i)$$

To calculate $\det(A_k)$, we replace the kth column with $b_i$s which in this case are all $0$s and last entry $1$. If we calculate the determinant using the kth column, we need only consider the determinant using the last entry as all the other ones will multiply with $0$ and become $0$. This last entry sub determinant also turns out to be a vandermonde determinant of one lower degree. So calculating the determinant using that

$$\det(A_k) = (-1)^{n+k}\prod_{1\leq i<j\leq n}(a_j-a_i)$$

where both $i,j\neq k$

When you divide them, all the terms that include $a_k$ are all that are left.

$$x_k = \left[(-1)^{n+k}\left(\prod_{k+1\leq j\leq n}(a_j-a_k) \prod_{1\leq i\leq k-1}(a_k-a_i)\right)\right]^{-1}$$

The terms which have greater index than $a_k$ come under one umbrella with the greater index term leading and the ones with lower come under a second umbrella with $a_k$ leading.

Rearrange all the terms in first umbrella so that $a_k$ term is leading and take all the $-1$s that come out and multiply it with existing to get your answer .

$$x_k = \left[(-1)^{n+k}\left((-1)^{n-(k+1)}\prod_{k+1\leq j\leq n}(a_k-a_j) \prod_{1\leq i\leq k-1}(a_k-a_i)\right)\right]^{-1}$$

$$x_k = \left[(-1)^{n+k+n-k-1}\left(\prod_{k+1\leq j\leq n}(a_k-a_j) \prod_{1\leq i\leq k-1}(a_k-a_i)\right)\right]^{-1}$$

$$x_k = \left[(-1)^{2n-1}\left(\prod_{k+1\leq j\leq n}(a_k-a_j) \prod_{1\leq i\leq k-1}(a_k-a_i)\right)\right]^{-1}$$

$$x_k = \left[\prod_{1\leq i\leq n, i\neq k}(a_i-a_k)\right]^{-1}$$

$\endgroup$
  • $\begingroup$ There might be a $-1$ multiplication/divide error $\endgroup$ – Sauhard Sharma Nov 14 '18 at 19:27

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.